Endoscopically assisted extracapsular dissection of pleomorphic adenoma of the parotid gland through a postauricular sulcus approach in young patients. Issue 4 (May 2017) - Chen, W.-l.; Fan, S.; Zhang, D.-m.
Abstract: We evaluated the aesthetic outcomes in 11 young patients (mean (range) age 21.7 (16–28) years) who had endoscopically assisted extracapsular dissection of benign pleomorphic adenomas of the parotid gland through a postauricular sulcus approach. The tumours varied in size from 1.5 × 1.0 cm to 2.5 × 2.0 cm, and all were removed completely without rupture. The cosmetic result was excellent in 10 patients and good in one. Patients were followed up for eight to 40 months, and there was no recurrence. The technique is simple and feasible, and it achieves excellent aesthetic results in young patients.